THE ROLE OF LIQUIDITY AND ITS MULTIPLE DIMENSIONS IN STOCK RETURNS: A STUDY WITH PANEL DATA OF THE BRAZILIAN MARKET - Vieira, Kelmara Mendes (2015)
Considering that the liquidity is a multidimensional measure, this study aims to evaluate the role of the said liquidity, using different measures and verifying if its use influences the results. The paper analyzes the influence of liquidity in stock returns in the Brazilian’s financial market, using the measure proposed by Amihud (2002), as well as the traditional measures, such as financial volume, number of trades, the spread and the turnover. Therefore, we used data from December 1994 to April 2010 of the stocks traded on the Securities, Commodities and Futures Exchange (BM&FBOVESPA). We concluded that the expected market illiquidity, as well as the spread has positive and statistically significant impact on stock returns. Meanwhile, the unexpected market illiquidity, just like the number of trades has a negative and statistically significant impact on the stock returns.